South African Consumer Adoption of Plant-Based and Cultivated Meat: A Segmentation Study - Szejda, Keri; Stumpe, Moritz; Raal, Ludwig; Tapscott, Claire E. (Frontiers in Sustainable Food Systems, 2021)
The purpose of this study was to assess the likelihood of consumer adoption of plant-based and cultivated meat in South Africa as a pathway to a healthy, sustainable, and equitable food supply. We recruited a large sample of South Africans representative across age (18–61), gender, race, and income to participate in an online survey. Participants responded to a range of measures including adoption indicators, estimated yearly intake, motivators for purchasing, desired product characteristics, preferred species, and sociodemographics. We found a high degree of openness to both products. For plant-based meat, 67% were highly likely to try and 59% were highly likely to purchase. For cultivated meat, 60% were highly likely to try and 53% were highly likely to purchase. The highest acceptance was amongst the younger generations: 60% of born-frees, 62% of millennials, and 53% of Gen X were highly likely to purchase plant-based meat and 55% of born-frees, 55% of millennials, and 46% of Gen X were highly likely to purchase cultivated meat. For the general population, we observed that future meat intake was estimated to be split equally among the three meat categories (conventional, cultivated, and plant-based). We found early adopters (those highly likely to purchase) to be quite similar in attitudinal and sociodemographic characteristics in comparison to the general population. The study findings suggest that both plant-based and cultivated meat could be viable market-based options for improving the food system in South Africa, as consumers across all segments of society, and especially amongst the younger population, indicated broad acceptance.